PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN ARTIKEL KIMIA TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI SISTEM KOLOID - Sri Yuliani Astuti; Muhali Muhali; Ratna Azizah Mashami (Prosiding Seminar Nasional Lembaga Penelitian Dan Pendidikan (LPP) Mandala)
The learning method that teachers tend to use were expository and question and answer method. It impact many students become passive without being able to develop the ability so effected their learning outcomes. This study aimed to determine the influence of learning model Problem Solving assisted chemistry articles to critical thinking skills of students. This research was quasi experiment with pretest-posttest control group design. Population of this study was all students of grade XI IPA totaling 243 students were divided into five classes. Sampling used was cluster random sampling so class XI IPA 5 as experimental group and class XI IPA 4 as control group. The data collection technique using description test. Data were analyzed with SPSS 16.0 for Windows at significant level of 5%. Initial test data were analyzed using t test. The results of the initial skills data analysis was significant value of 0.011 which means there were differences between the experimental group and control group. The final skills data were analyzed using Anacova test. The results of the final critical thinking skills data analysis was significant value of 0.000 which means there were differences between the experimental group and control group. Based on the study results concluded the learning model Problem Solving assisted chemistry articles influence to critical thinking skills of students in colloidal systems concept.